Enhancing immigrant families’ mental health through the promotion of structural and community-based support - Kerker, Bonnie D.; Barajas-Gonzalez, R. Gabriela; Rojas, Natalia M.; Norton, Jennifer M.; Brotman, Laurie M. (Frontiers in Public Health, 2024)
Immigrant communities in the US are diverse and have many assets. Yet, they often experience stressors that can undermine the mental health of residents. To fully promote mental health and well-being among immigrant communities, it is important to emphasize population-level policies and practices that may serve to mitigate stress and prevent mental health disorders. In this paper, we describe the stressors and stress experienced by immigrant families, using Sunset Park, Brooklyn as an example. We discuss ways to build structures and policies in support of equitable environments that promote mental health at the population level and enable families and their children to thrive.